Improvement of farm homes - Rhoades, W.J. (My University, 1897)
Introduction: …In the midst of all this we wonder how many ever consider for a moment the cause of the dissatisfaction with country life. A close observer, after an hour drive in the country might answer all inquiries. The average far home is an unsightly place. It is too often built on that part of the farm, which the farmer from an economical point of view considers fit for nothing else. A low, flat stagnant place, or else a clay or rock hill is generally a chosen site. And more often still, where the site of the farm home has been selected with consideration as to sanitary conditions and conditions adapted to decorative planting and improvement, they have been grossly neglected. For instance here is a farm home situated on a gentle raise from the public high way. There is good drainage, and abundance of pure water. But the house and out buildings have been thrown together without a plan and are unpainted and repulsive to see. There is no yard fence, a hog pen in close proximity and the poultry runs at will. Probably a few ugly trees have resisted the unfavorable conditions and have forced their existence. Shrubbery has never been planted and a pretty bed of flowers is unknown. Instead of the shrubbery and pretty bed of flowers, is a profusion of rubbish and litter the result of years of accumulation, with perhaps here and there a broken reaper or some other implement bleaching in the sun. This is not a picture of all farm homes but is it about an average.
Citation: Rhoades, W.J. Improvement of farm homes. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Farm homes; Site; Landscaping; Maintenance; Theses; Manuscripts (documents)